‘Guilty Women’, Foreign Policy, and Appeasement in Inter-War Britain - Gottlieb, Julie V. author. aut Link
336 p.
Keywords: British women were deeply invested in foreign policy between the wars. This study casts new light on the turn to international affairs in feminist politics, the gendered representation and experience of the Munich Crisis, and the profound impression made by female public opinion on PM Neville Chamberlain in his negotiations with the dictators.